2005
DOI: 10.2139/ssrn.861664
|View full text |Cite
|
Sign up to set email alerts
|

Japan's Deflation, Problems in the Financial System and Monetary Policy

Abstract: On 18-19 June 2004, the BIS held a conference on "Understanding Low Inflation and Deflation". This event brought together central bankers, academics and market practitioners to exchange views on this issue (see the conference programme in this document). This paper was presented at the workshop. The views expressed are those of the author(s) and not those of the BIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 22 publications
0
50
0
1
Order By: Relevance
“…It seems to be a case of "bad" deflation characterized by stagnant real activity along with mild deflation (Ahearne et al (2002)). Arguably, the underlying cause of the Japanese problem was not deflation, per se, but the problems in the banking system with its concomitant adverse consequences for the monetary transmission mechanism (Hetzel (2004), Sellon (2004), Baba et al (2004)). 41 The continued weakness of the Japanese banking system, ie the inability to close or recapitalize insolvent banks, may have hampered the Bank of Japan's ability to stimulate bank lending.…”
Section: Box 1 Recent Deflation Experiencesmentioning
confidence: 99%
“…It seems to be a case of "bad" deflation characterized by stagnant real activity along with mild deflation (Ahearne et al (2002)). Arguably, the underlying cause of the Japanese problem was not deflation, per se, but the problems in the banking system with its concomitant adverse consequences for the monetary transmission mechanism (Hetzel (2004), Sellon (2004), Baba et al (2004)). 41 The continued weakness of the Japanese banking system, ie the inability to close or recapitalize insolvent banks, may have hampered the Bank of Japan's ability to stimulate bank lending.…”
Section: Box 1 Recent Deflation Experiencesmentioning
confidence: 99%
“…A pioneering work by Hayashi and Prescott (2002), based on a simple growth model, showed that movements of total factor productivity (hereafter TFP), which are regarded as exogenous changes in the technology level in their model, explains the bulk of output decline from the early 1990s onward. 2 Braun and Shioji (2007) obtained a similar result based a growth model in which two classes of technology, investment-speci…c technology and TFP, drive macroeconomic ‡uctuations in Japan. From the perspective of a New Keynesian framework, Sugo and Ueda (2008) estimate a model that is close to the model of Smets and Wouters (2005) using Japanese data and show that TFP shocks and investment adjustment cost shocks are the two important shocks that account for output ‡uctuations in Japan.…”
Section: Introductionmentioning
confidence: 77%
“…Baba et al (2005) and Oda and Ueda (2007) find that BoJ purchases had little effect on long-term yields. It is hard to distinguish the partial effect of central bank bond purchases from the powerful effect of the central bank's commitment essentially to keep the overnight rate at zero until the return of inflation (the so-called policy duration effect).…”
Section: Japanese Debt Management Since 2000 and Boj Jgb Purchasesmentioning
confidence: 98%